2018
DOI: 10.1371/journal.pone.0194679
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β1/CD105 signaling controls vascular network formation within growth factor sequestering hyaluronic acid hydrogels

Abstract: Cell-based strategies for the treatment of ischemic diseases are at the forefront of tissue engineering and regenerative medicine. Cell therapies purportedly can play a key role in the neovascularization of ischemic tissue; however, low survival and poor cell engraftment with the host vasculature following implantation limits their potential to treat ischemic diseases. To overcome these limitations, we previously developed a growth factor sequestering hyaluronic acid (HyA)-based hydrogel that enhanced transpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 76 publications
2
29
0
Order By: Relevance
“…To date, most studies published on endoglin have focused on L-endoglin, although L-endoglin and S-endoglin are co-expressed and distinguishable in vivo 32,36,37,[39][40][41][42][43]48,[50][51][52] . This finding explains the contradictory results in the quantitative expression of endoglin in experimental BPD models or postmortem BPD patients in which the total quantity of endoglin has been evaluated 9,11,18,25,32,40,42,45,53 .…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…To date, most studies published on endoglin have focused on L-endoglin, although L-endoglin and S-endoglin are co-expressed and distinguishable in vivo 32,36,37,[39][40][41][42][43]48,[50][51][52] . This finding explains the contradictory results in the quantitative expression of endoglin in experimental BPD models or postmortem BPD patients in which the total quantity of endoglin has been evaluated 9,11,18,25,32,40,42,45,53 .…”
Section: Discussionmentioning
confidence: 98%
“…Evidence indicates that L-endoglin, the predominant isoform in ECs, promotes EC proliferation via TGFβ-ALK1 signalling, whereas S-endoglin acts as an antagonist of L-endoglin via activation of the TGFβ-ALK5 pathway 32,33,36,37 .To date, most studies published on endoglin have focused on L-endoglin. It has been found that L-endoglin enhances ALK1-Smad1/5 signalling in ECs, leading to proliferation and migration, which are the main characteristics of the activation phase of angiogenesis 15,18,20,22,[38][39][40][41][42][43] . However, a role of S-endoglin during endothelial senescence was recently described 36,37 .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The affinitybound TGF-β1 induces an initial response on progenitor cells, which is then amplified by the sequestering of proangiogenic GFs produced endogenously in response to the initial stimulation. [101][102][103] This provides a good example of the emerging trends of ECM-inspired microenvironment manipulation for control of stem/progenitor cell behavior. To prepare these gels, HA was modified with acrylate groups while heparin was thiolated, with thiol-ene chemistry being used to link the two polymeric components.…”
Section: Platforms With Inclusion Of Ecm Componentsmentioning
confidence: 99%